Molecular Technique as A Vigorous Instrument for Identification and Classification of Dickeya on The Ornamental Plants - Noor Febryani; Yuichi Takikawa (Jurnal Biologi Tropis, 2023)
Information on the genetic diversity of pathogenic bacteria causing plant disease is rare to find. This study aims to identify and classify disease-causing pathogens in several ornamental plants molecularly. Sixteen bacterial strains were isolated from carnation, chrysanthemum, and kalanchoe. All strains were grouped in D. dianthicola although the carnation strains and kalanchoe strains gave different results from the identified carnation strains. The differences were found in rep-PCR and 16S rDNA. Band patterns produced by rep-ERIC PCR revealed that the carnation strains, chrysanthemum strains, and kalanchoe strains formed slightly different from the identified carnation strains. Meanwhile, sequence analysis of 16S rDNA revealed that the carnation strains and kalanchoe strains were grouped separately from the identified carnation strains. Even though they were positioned independently from the identified carnation strains and other D. dianthicola strains, but they have closely related each other thus they are identified as a specific group of D. dianthicola. However, based on multilocus sequence analysis (MLSA) of dnaX, recA, gyrB and rpoD, all strains were grouped into D. dianthicola.  Furthermore, the result of pathogenicity test showed that all strains were pathogenic to carnation, potato, and chrysanthemum, but they were not pathogenic to kalanchoe.